Poetyckie penetracje. Literatura, jej tłumacze i wydawcy na frontach Wielkiej Wojny - Zajas, Paweł (My University, 2012)
The author analyses the mechanisms of German cultural politics during World War I on the basis of unpublished archival materials on Belgian-german and German-Polish literary transfer. This historical presentation served to formulate more general theoretical conclusions about the transnational character of the cultural exchange during the growing nationalistic stimulation of societies as well as to put forward some scholarly postulates addressing the methodology of cultural transfer and Histoire croisée at the turn of 19th century.
Keywords: World War I